Zoomorphism, Biomimetics and Computational Design - Benedetta Terenzi; Saverio Mecca (Agathón)
The article explores the main stages of human production focusing on the relationship between man and animal, demonstrating how it has stimulated the emergence of new technical and expressive solutions. In architecture, the image of the animal has been used both in allegorical and structural terms: from the Sphinx to the humanistic-Renaissance representations, Art Nouveau to biomorphic architecture. It has likewise inspired the formalization of furnishings: from the animalières and zoomorphic propositions to the bionic that reinterprets the structure and mechanical behaviour, to the computational design experiments that shape the natural behaviors distilled in algorithms.